Development of a mechanical setup for assessing stiffness of the wrist joints from torque and kinematic measurements - Chan, Wai Keat. (2011)
The objective of this project is to design and to develop a passive mechanical setup for assessing stiffness of the wrist joints. As previous studies have performed the measurement by depending on the torque motor, the primary aim of the project is to design the passive structure with manual stretching instead of a motor. To investigate the accuracy of the setup, a known mass-spring system is simulated as human wrist. Based on the mass-spring system, validation tests for static and continuous perturbation in flexion – extension are examined. Torque – angle relations from the static measurement shows good accuracy as the observation values are in close proximity to the simulation result. The results for slow continuous perturbation show a consistent hysteresis loop which is possibly caused by the static friction in the hardware while the curve for fast perturbation produces analogous pattern with the simulated curve and hysteresis is not observed in fast perturbation compared to the slow perturbation. This can be explained that the static friction is overcome by the faster movement, hence producing a better result. The findings suggest that the measurements of stiffness component during manual stretching using the passive mechanical setup is accurate and could be clinically useful in evaluating wrist joint stiffness.